Factors affecting Human Resource Development of Mechanical Enterprises in Vietnam - Van, Vu Hong; Lan, Dinh Ngoc (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
The aim of this study is to determine factors influencing human resource development of mechanical enterprises in Vietnam. The 392 usable data were collected; the Exploratory Factor Analysis (EFA) and the model and hypotheses were tested with Pearson’s Correlation Coefficient. The research findings indicated that four factors affecting human resource development of mechanical enterprises including (i) Technology, (ii) Learning Motivation, (iii) Learning Culture of the enterprise and (iv) Abilities of employees. Furthermore, recommendations are proposed to enhance human resource development in mechanical enterprises.